2005
DOI: 10.1021/ja0543604
|View full text |Cite
|
Sign up to set email alerts
|

ZiCo:  A Peptide Designed to Switch Folded State upon Binding Zinc

Abstract: We describe a novel approach to the design of a metal-triggered conformational switch. Specifically, two distinct protein-folding motifs were merged into one polypeptide sequence. The target structures were an alpha-helical coiled-coil trimer and zinc-bound monomer. Solution-phase spectroscopic, sedimentation, and binding studies confirmed the key aspects of the design. Both forms of the peptide were cooperatively folded, and the switch between them was reversible. This design process potentially presents a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 32 publications
1
85
0
1
Order By: Relevance
“…In the prion protein example, the driving force for the conformational switch from monomer to aggregate is extensive interaction of the edges of outer ␤-strands in the aggregated state. Metal binding has also been demonstrated to mediate major changes in secondary, tertiary, and quaternary structure in computationally designed proteins (30)(31)(32). Although our results show a switch from one monomeric fold into another, the energetic situation is similar in some ways to conformation switching driven by ligand binding.…”
Section: Discussionmentioning
confidence: 50%
“…In the prion protein example, the driving force for the conformational switch from monomer to aggregate is extensive interaction of the edges of outer ␤-strands in the aggregated state. Metal binding has also been demonstrated to mediate major changes in secondary, tertiary, and quaternary structure in computationally designed proteins (30)(31)(32). Although our results show a switch from one monomeric fold into another, the energetic situation is similar in some ways to conformation switching driven by ligand binding.…”
Section: Discussionmentioning
confidence: 50%
“…Furthermore, monomeric proteins sometimes can assume alternative conformations in a multimeric form. This is observed in prion proteins and with monomeric and dimeric forms of the chemokine lymphotactin (30) and also with proteins designed to switch conformation and quaternary structure in the presence of a transition metal (31,32). It has also been shown that five mutations to the core of G B result in a conformational change to a stable, intertwined tetrameric state (33).…”
Section: Discussionmentioning
confidence: 96%
“…The CD spectrum of RG13 changes only slightly in the presence of zinc, suggesting that zinc-binding induces more subtle changes in structure than those observed in designed zinc-dependent conformational switches (Cerasoli et al 2005; Ambroggio and Kuhlman 2006). RG13's K i and K d for Zn 2+ match, suggesting the Zn 2+ -binding sites being observed by the two methods are the same.…”
Section: Allosteric Signaling In Rg13mentioning
confidence: 96%